2009
DOI: 10.1128/cvi.00023-08
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Polyribosylribitol Phosphate Antibody Concentrations and Avidities in Children since the Start ofHaemophilus influenzaeType b Immunization of Infants in the United Kingdom

Abstract: The introduction of routine infant immunization with Haemophilus influenzae type b (Hib) conjugate vaccines in the United Kingdom in 1992 led to a significant reduction in invasive disease due to this organism. Subsequently, between 1999 and 2003 there was an increase in the number of immunized children with Hib infection. We investigated whether the rise in cases was related to changes in anti-polyribosylribitol phosphate (PRP) antibody concentration or avidity. Using stored sera, we analyzed temporal changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…20,21 Studies undertaken in children in Kathmandu have demonstrated an Hib carriage prevalence of between 4.1 and 8.9% depending on the age group and population studied. 16,22 This is similar to the prevalence seen in other areas of the world where Hib is known to be a significant cause of meningitis and pneumonia.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…20,21 Studies undertaken in children in Kathmandu have demonstrated an Hib carriage prevalence of between 4.1 and 8.9% depending on the age group and population studied. 16,22 This is similar to the prevalence seen in other areas of the world where Hib is known to be a significant cause of meningitis and pneumonia.…”
supporting
confidence: 77%
“…The United Kingdom incorporated routine infant HibCV (at 2, 3 and 4 months) in 1992, which lead to a dramatic decline in the annual incidence of invasive Hib disease (from 28.3/100,000 in the preimmunization era to 0.97/100,000 by 1998 in children under 5 years of age). 16 However, this was followed by a year-byyear increase in the incidence of invasive Hib (from 1999 to 2003). The cause was likely to have been multifaceted, occurring at a time when there was no booster inclusion and acellular pertussis combination vaccines with group C meningococcal vaccine being newly introduced, potentially leading to interference with Hib responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protective antibody concentrations (short-term and long-term protective thresholds) were > 0.15 µg/mL and > 1.0 µg/mL, respectively. Anti-PRP antibody concentrations in serum were determined by using a standard protocol (10,11).…”
Section: Antibody Measurementmentioning
confidence: 99%
“…4,5 Hib polysaccharide-protein conjugate vaccines developed in the 1980s stimulate a T cell-dependent immune response, which leads to immunologic memory, and an immunoglobulin class switch with resultant increased antibody affinity and avidity. [6][7][8][9][10] Accordingly, Hib conjugate vaccines are highly immunogenic, even in young infants. [11][12][13] Introduction of Hib conjugate vaccines into the routine immunization schedule has led to near eradication of invasive Hib disease in many industrialized and transitional countries, and some developing countries.…”
Section: Introductionmentioning
confidence: 99%